AN ANALYSIS OF STRATEGIES, OPPORTUNITIES, AND CHALLENGES RELATED TO RURAL MARKETING IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Rural marketing refers to the process of marketing products and services to consumers in rural areas. Rural areas are typically characterized by lower population densities, agricultural-based economies, and limited access to modern infrastructure and technology. As the urban market becomes more competitive, the Businesses want to expand into the rural market with their products. The past few years, Rural markets have benefited from the economy's overall growth, that has resulted in a considerable rise in rural communities' purchasing power. The Green Revolution has led to an increase in the consumption of manufactured goods in rural India. The rural market landscape of today is evolving at a very fast pace. It is quite tough for businesses to pass up the opportunities they possibly from markets in remote areas. The companies must overcome certain challenges.